Emotion Regulation, Physical Diseases, and Borderline Personality Disorders: Conceptual and Clinical Considerations - Cavicchioli, Marco; Barone, Lavinia; Fiore, Donatella; Marchini, Monica; Pazzano, Paola; Ramella, Pietro; Riccardi, Ilaria; Sanza, Michele; Maffei, Cesare (Frontiers in Psychology, 2021)
This perspective paper aims at discussing theoretical principles that could explain how emotion regulation and physical diseases mutually influence each other in the context of borderline personality disorder (BPD). Furthermore, this paper discusses the clinical implications of the functional relationships between emotion regulation, BPD and medical conditions considering dialectical behavior therapy (DBT) as a well-validated therapeutic intervention, which encompasses these issues. The inflexible use of maladaptive emotion regulation strategies (e.g., suppression, experiential avoidance, rumination) might directly increase the probability of developing physical diseases through a physiological pathway, or indirectly through a behavioral pathway. Some metabolic and chronic medical conditions could significantly impact emotional functioning through biological alterations involved in emotion regulation. Several empirical studies have shown high co-occurrence rates between BPD and several chronic physical diseases, especially ones linked to emotion-based maladaptive behaviors. DBT addresses physical diseases reported by individuals with BPD reducing problematic behaviors functionally associated to emotion dysregulation and identifying physical health as a goal for Building a Life Worth Living.